Additional Inferior Extensor Retinaculum Augmentation after All-Inside Arthroscopic Anterior Talofibular Ligament Repair for Chronic Ankle Instability is Not Necessary. Issue 1 (January 2022) - Lee, Sung Hyun
Category: Ankle; Arthroscopy; Sports Introduction/Purpose: Although several arthroscopic surgical techniques for the treatment of chronic ankle lateral instability (CAI) have been introduced recently, the effect of inferior extensor retinaculum (IER) augmentation remains unclear. The purpose of this study was to compare the clinical outcomes after arthroscopic anterior talofibular ligament (ATFL) repair according to whether additional IER augmentation was performed or not. Methods: Between 2016 and 2018, we performed a retrospective review of consecutive patients who underwent arthroscopic ATFL repair surgery for CAI. The mean age of the patients was 35.2 years (range, 19-51 years), and the mean follow-up period was 32.6 months (range, 24-48 months). Patients were divided into two groups according to the surgical technique used for CAI: Arthroscopic ATFL repair (group A, n = 37), and arthroscopic ATFL repair with additional IER augmentation (group R, n = 45). The Pain Visual Analog Scale, American Orthopaedic Foot & Ankle Society (AOFAS) score, Foot and Ankle Outcome score (FAOS), and the Karlsson Ankle Functional Score were measured as subjective outcomes, and posturographic analysis was performed using a Tetrax device as an objective outcome. Radiologic outcome evaluations were performed preoperatively and at 2 years postoperatively using stress radiographs and axial view MRI. Results: Out of 101 patients, 19 (18.5%) were excluded based on the exclusion criteria, and 82 patients were evaluated. We identified a total of six re-tears (7.3%) based on postoperative MRI evaluation. All patients who had ATFL re-tear on MRI (8.1% [3/37] in group A, and 6.7% [3/45] in group R) demonstrated recurrent CAI with functional discomfort and anterior displacement > 3 mm compared to the intact contralateral ankle. All clinical scores and posturography results were improved after surgery in both groups (P < 0.001). However, there were no significant differences in the clinical results and radiologic findings between the two groups. Conclusion: The clinical and radiologic outcomes of patients with CAI improved after all-inside arthroscopic ATFL repair. However, additional IER augmentation after arthroscopic ATFL repair did not guarantee better clinical outcomes.